2011
DOI: 10.1016/j.talanta.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A novel biosensor based on serum antibody immobilization for rapid detection of viral antigens

Abstract: In this paper, we represent a label-free biosensor based on immobilization of serum antibodies for rapid detection of viral antigens. Human serum containing specific antibodies against Japanese encephalitis virus (JEV) was immobilized on a silanized surface of an interdigitated sensor via protein A/glutaraldehyde for electrical detection of JEV antigens. The effective immobilization of serum antibodies on the sensor surface was verified by Fourier transform infrared spectrometry and fluorescence microscopy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 46 publications
(40 reference statements)
2
31
0
Order By: Relevance
“…Such change would lead to a corresponding increase in the absorbance intensity at 427 nm (Figure 8(a)) (Huy et al 2011). Similar optical absorption characteristics had been reported for the detection of fibrinogen using gold nanoparticles (Hrapovic et al 2003). )…”
Section: Detection Of Jev Antigensupporting
confidence: 72%
See 1 more Smart Citation
“…Such change would lead to a corresponding increase in the absorbance intensity at 427 nm (Figure 8(a)) (Huy et al 2011). Similar optical absorption characteristics had been reported for the detection of fibrinogen using gold nanoparticles (Hrapovic et al 2003). )…”
Section: Detection Of Jev Antigensupporting
confidence: 72%
“…The limit of detection (LOD) of Ag NPs-based sensing probes defined as 3 σ/s, was calculated to be 12.8 ng/mL. The LOD value for JEV antigen detection reported here is comparable and within the range of 0.75 to 10 ng/mL for reported electrochemical biosensors (Huy et al 2011;Li et al 2011;Tran et al 2012). Nevertheless, the novel Ag NPs-based sensing probe reported herein is fabricated using a comparatively simple fabrication process involving a facile silanization step for depositing Ag NPs onto glass/mica slides without the need of any sophisticated instruments such as chemical vacuum depositor and requires fewer immobilization steps.…”
Section: Detection Of Jev Antigensupporting
confidence: 57%
“…This result demonstrated that the proposed biosensor strip exhibited rapid responses, and results of the analysis were obtainable within 10 minutes. This observed response time is considerably faster than that reported for interdigitated biosensor at 20 minutes [10] and other JEV diagnosis methods which require diagnosis times ranging from hours to days [14]. The substantially enhanced sensitivity and faster response time could be attributed to the use of CNPs which enabled a higher loading of JEV antibody as well as the increased overall electrical conductivity of the SPCE biosensor strip.…”
Section: Resultsmentioning
confidence: 75%
“…Recently, an electrochemical biosensor was fabricated for rapid detection of JE antigen by immobilized serum antibody on a silanized surface of an interdigitated sensor with a detection limit of 0.75 gmL −1 within 20 minutes [10]. In another study, goldcoated magnetite beads were used for the immobilization of JEV antibody and multiwall carbon nanotubes (MW-CNT) were used to improve the signal as well as the conductivity of electrochemical biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, immunosensors based on electrochemical detection have the advantage of being highly sensitive, rapid, inexpensive and highly amenable to micro-fabrication, and it is also easy to measure the changes in electrical/electrochemical properties resulting from the antigen-antibody reaction on the surface of the sensor [1,3]. However, the electrochemical signal obtained from the reaction of antigen-antibody binding is normally very small.…”
Section: Introductionmentioning
confidence: 99%